Patterns of delay in early gross motor and expressive language milestone attainment in probands with genetic conditions versus idiopathic ASD from SFARI registries. (12th August 2021) - Wickstrom, Jordan; Farmer, Cristan; Green Snyder, LeeAnne; Mitz, Andrew R.; Sanders, Stephan J.; Bishop, Somer; Thurm, Audrey
Abstract : Background: Recent large‐scale initiatives have led to systematically collected phenotypic data for several rare genetic conditions implicated in autism spectrum disorder (ASD). The onset of developmentally expected skills (e.g. walking, talking) serve as readily quantifiable aspects of the behavioral phenotype. This study's aims were: (a) describe the distribution of ages of attainment of gross motor and expressive language milestones in several rare genetic conditions, and (b) characterize the likelihood of delays in these conditions compared with idiopathic ASD. Methods: Participants aged 3 years and older were drawn from two Simons Foundation Autism Research Initiative registries that employed consistent phenotyping protocols. Inclusion criteria were a confirmed genetic diagnosis of one of 16 genetic conditions (Simons Searchlight) or absence of known pathogenic genetic findings in individuals with ASD (SPARK). Parent‐reported age of acquisition of three gross motor and two expressive language milestones was described and categorized as on‐time or delayed, relative to normative expectations. Results: Developmental milestone profiles of probands with genetic conditions were marked by extensive delays (including nonattainment), with highest severity in single gene conditions and more delays than idiopathic ASD in motor skills. Compared with idiopathic ASD, the median odds of delay among the genetic groups were higher by 8.3 times (IQR 5.8–16.3) for sitting, 12.4 times (IQR 5.3–19.5) for crawling, 26.8 times (IQR 7.7–41.1) for walking, 2.7 times (IQR 1.7–5.5) for single words, and 5.7 times (IQR 2.7–18.3) for combined words. Conclusions: Delays in developmental milestones, particularly in gross motor skills, are frequent and may be among the earliest indicators of differentially affected developmental processes in specific genetically defined conditions associated with ASD, as compared with those with clinical diagnoses of idiopathic ASD. The possibility of different developmental pathways leading to ASD‐associated phenotypes should be considered when deciding how to employ specific genetic conditions as models for ASD.